Flute instrumental music relaxation effectively reduces anxiety in premenopausal women - Nuraeni, Witri; Mulyani, Nunung; Suptiani, Laila Putri (Jurnal Kesehatan Ibu dan Anak, 2025)
Premenopausal women often experience heightened anxiety due to hormonal fluctuations and psychosocial stressors related to the menopausal transition. Non-pharmacological interventions, particularly music therapy, have been recognized as an effective complementary approach to promote emotional well-being. However, limited empirical evidence exists on the specific effect of flute instrumental music relaxation among premenopausal women in community health settings. This study aimed to determine the effectiveness of flute instrumental music relaxation therapy in reducing anxiety levels among premenopausal women. A quasi-experimental pretest–posttest design was applied involving 51 premenopausal participants selected through purposive sampling in the Mangkubumi Public Health Center service area, Tasikmalaya City, Indonesia in 2025. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after seven consecutive days of flute instrumental music relaxation therapy. Data were analyzed using the Wilcoxon signed-rank test after confirming non-normal distribution via the Kolmogorov–Smirnov test. Respondents were predominantly aged 40–45 years (54.9%). The mean anxiety score before the intervention was 16.25 (SD = 2.30), categorized as mild anxiety, and decreased to 12.43 (SD = 1.62) post-intervention, indicating no anxiety. The Wilcoxon test revealed a statistically significant reduction in anxiety levels (Z = –3.82, p < 0.001). The mean reduction of 3.82 points demonstrates a meaningful therapeutic effect of the flute music intervention. These findings align with prior studies reporting music’s role in regulating stress responses, modulating neuroendocrine pathways, and improving emotional stability among menopausal and perimenopausal women. The result emphasizes the cultural appropriateness and accessibility of flute music as a relaxation medium within Indonesia’s maternal and reproductive health services. Flute instrumental music relaxation effectively reduces anxiety among premenopausal women and represents a feasible, low-cost intervention for community-based midwifery and women’s health programs. Future research should utilize randomized controlled designs, explore long-term outcomes, and compare different musical modalities to enhance evidence-based integration into reproductive health care.